2009
DOI: 10.1093/chemse/bjp060
|View full text |Cite
|
Sign up to set email alerts
|

Plant Terpenes Affect Intensity and Temporal Parameters of Pheromone Detection in a Moth

Abstract: In moths, the components of the female pheromone blend are detected in the male antennae by pheromone olfactory receptor neurons (Ph-ORNs) expressing narrowly tuned olfactory receptors. Responses to sex pheromones have generally been thought to be independent from the odorant background. However, interactions between pheromone components and plant volatiles have been reported at behavioral and detection levels. To document the mechanisms of such interactions, we analyzed Ph-ORN responses of Spodoptera littoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 46 publications
4
70
2
Order By: Relevance
“…The resolution of pulsed pheromone stimuli further improved when heptanal was added, especially for A2 neurons, because of the shortening of the E1 phase and the lengthening of the following inhibition. In S. littoralis, an improvement of pulse resolution in pheromone specific ORNs was also found when pheromone stimuli were applied in a plant odour background (Party et al, 2009;Rouyar et al, 2011). The contrast enhancement between the single spike trains emitted in response to the discontinuous mixture signal in A2 neurons in A. ipsilon is amplified at the neuron population scale.…”
Section: Plant Odour Enhances the Response Contrast During Pulsed Phementioning
confidence: 78%
See 4 more Smart Citations
“…The resolution of pulsed pheromone stimuli further improved when heptanal was added, especially for A2 neurons, because of the shortening of the E1 phase and the lengthening of the following inhibition. In S. littoralis, an improvement of pulse resolution in pheromone specific ORNs was also found when pheromone stimuli were applied in a plant odour background (Party et al, 2009;Rouyar et al, 2011). The contrast enhancement between the single spike trains emitted in response to the discontinuous mixture signal in A2 neurons in A. ipsilon is amplified at the neuron population scale.…”
Section: Plant Odour Enhances the Response Contrast During Pulsed Phementioning
confidence: 78%
“…Evidence for inhibitory effects of plant compounds on pheromone responses in antennal sensilla responding exclusively to pheromone compounds has been found in several moth species (e.g. Pophof and van der Goes van Naters, 2002;Party et al, 2009), including A. ipsilon, using single sensillum recordings (Deisig et al, 2012). Optical imaging studies have also shown that the input of pheromone information to the AL is reduced when adding plant odours (Deisig et al, 2012).…”
Section: Mgc Neurons Are Sensitive To a Behaviourally Relevant Plant mentioning
confidence: 99%
See 3 more Smart Citations